T-Cell Immunity to Infection with Dengue Virus in Humans - Weiskopf, Daniela; Sette, Alessandro (Frontiers in Immunology, 2014)
Dengue virus (DENV) is the etiologic agent of dengue fever, the most significant mosquito-borne viral disease in humans. Up to 400 million DENV infections occur every year, and severity can range from asymptomatic to an acute self-limiting febrile illness. In a small proportion of patients, the disease can exacerbate and progress to dengue hemorrhagic fever (DHF) and/or dengue shock syndrome (DSS), characterized by severe vascular leakage, thrombocytopenia, and hemorrhagic manifestations. A unique challenge in vaccine development against DENV is the high degree of sequence variation, characteristically associated with RNA viruses. This is of particular relevance in the case of DENV since infection with one DENV serotype (primary infection) presumably affords life-long serotype-specific immunity but only partial and temporary immunity to other serotypes in secondary infections settings. The role of T cells in dengue virus infection and subsequent disease manifestations is not fully understood. According to the original antigenic sin theory, skewing of T cell responses induced by primary infection with one serotype causes less effective response upon secondary infection with a different serotype, predisposing to severe disease. Our recent study has suggested an HLA linked protective role for T cells. Herein we will discuss the role of T cells in protection and pathogenesis from severe disease as well as the implications for vaccine design.